Novel Insights into Mechanisms of Pain Caused by Radiotherapy - Jeffrey A. Foster; Sun H. Park; Joseph Moore; Kaitlyn E. Reno; Alicia Costa-Terryll; Leslie Kim; Michael T. Munley; Jeffrey S. Willey (Current Stem Cell Reports, 2026)
Purpose of Review Radiotherapy serves as a palliative option for alleviating cancer pain but can also elicit chest wall pain following stereotactic body radiotherapy (SBRT). The etiology of chest wall pain remains unclear but may relate to SBRT effects on normal ribs and responses from activated osteoclasts. This review explores potential mechanisms and treatment strategies for this increasingly common complication for patients undergoing radiotherapy. Recent Findings Radiation-induced bone loss is likely multifactorial, involving changes to bone microvasculature, suppressed angiogenesis, osteoblast damage and senescence, as well as increased resorption via activated osteoclasts. Preliminary data suggest that inhibiting osteoclasts may prevent radiation-induced chest wall pain and rib fracture. Our laboratory has identified TGF-βR1 as a potential central mediator of radiation-induced bone loss and pain signaling between osteoclasts and sensory neurons. Summary Advances in radiotherapy have optimized tumor targeting and control. However, radiation-induced musculoskeletal toxicity remains prevalent. Recent findings suggest targeted inhibition of TGF-β signaling between osteoclasts and neurons may offer a therapeutic strategy to mitigate radiation-induced pain.